Probiotic Administration Contributes to the Improvement in Intestinal Dysregulation Induced by Allergic Contact Dermatitis - Eduardo Mendes; Evelyn Roxana Perez Umana; Daniel Di Pace Soares Penna; Fernando Augusto de Oliveira; Leandro Nascimento Lemos; Willian Rodrigues Ribeiro; Mateus Barbosa Casaro; Mariana Lazarini; Valéria Maia Oliveira; Caroline Marcantonio Ferreira (Microorganisms)
Recent studies have emphasized the impact of gut microbiota on skin health, but the reverse, how skin diseases affect gut homeostasis, has received less attention. Allergic contact dermatitis (ACD), a common skin disorder affecting one in four people worldwide, can be accompanied by intestinal disturbances. To explore this, we used an experimental model of ACD to investigate the intestinal changes induced by the disease. Parameters assessed included intestinal microbiota, short-chain fatty acids (SCFAs), gene expression related to intestinal permeability, inflammatory cytokines, and mucus production. To evaluate potential therapeutic interventions, the probiotic Bifidobacterium longum strain BB536 was administered via gavage, starting 10 days before dermatitis induction and continuing until the last day of disease induction. ACD caused alterations in the composition of intestinal microbiota compared to naïve mice but did not affect SCFA production. The probiotic altered microbiota composition and increased acetate production in dermatitis-induced mice. ACD decreased the gene expression of TjP1, ATHO1, and MUC2, while probiotic treatment restored TjP1 and ATHO1 to normal levels. The cytokine IL-6 increased in the ACD group compared to naïve mice, whereas IL-10 decreased; probiotic treatment also restored these levels. Intestinal mucus production, affected by ACD, was partially restored by probiotic treatment. The findings suggest that probiotics could be a therapeutic strategy to prevent intestinal issues caused by skin diseases.